Myeloid derived suppressor cells and their role in tolerance induction in cancer - Fujimura, Taku; Mahnke, Karsten; Enk, Alexander (Journal of dermatological science, 2010)
Myeloid derived suppressor cells (MDSCs) comprise a phenotypically heterogeneous population of cells, which can be found in tumor-bearing mice and in patients with cancer. MDSCs play a central role in the induction of peripheral tolerance. Together with regulatory T cells (Tregs) they promote an immunosuppressive environment in tumor-bearing hosts. The phenotype of MDSCs differs in humans and mice, and the exact mechanisms of their suppressive function are still controversially discussed. In summary, MDSCs are a group of phenotypically heterogeneous cells of myeloid origin that have common biological activities. In this review, we discuss the definition of MDSCs, the proposed mechanisms of expansion and the recruitment and activation of MDSCs, as well as their biological activities in tumor-bearing hosts to assess the potential therapeutic applications.